1984
DOI: 10.1073/pnas.81.11.3404
|View full text |Cite
|
Sign up to set email alerts
|

Lampbrush loop-specific protein of Drosophila hydei.

Abstract: By immunofluorescence techniques and protein blotting experiments we have shown that an antiserum specifically reacts with a Mr 80,000 protein (the "Ps protein") in the lampbrush loop "pseudonucleolus" in spermatocyte nuclei of Drosophila hydei. Comparative studies of X/Y and X/0 testes indicate that the gene encoding the Ps protein is not located on the Y chromosome but on an autosome or the X chromosome. The Ps protein is tissue specific. It is likely to be a rather conserved protein since the antigenic dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…The peculiar molecular structure of the loop-forming regions, consisting of large portions of satellite DNA interspersed with transposable elements, is maintained in different Drosophila species, although the DNA sequences involved are very different (Hennig et al 1974;Vogt and Hennig 1983;Hujiser et al 1988;Lankenau et al 1990;Hochstenbach et al 1994). Another conserved feature of the lampbrush-like loops is their association with a number of non-Y-encoded antigens, which include DNA-interacting proteins (Marhold et al 2002), RNA-interacting proteins (Risau et al 1983;Melzer and Glätzer 1985;Bonaccorsi et al 1988;Eberhart et al 1996;Cheng et al 1998;Heatwole and Haynes 1996), and testis-specific antigens that are incorporated either in nuclei (Svensson et al 2003) or in sperm tails (Hulsebos et al 1984;Bonaccorsi et al 1988;Pisano et al 1993;Lu and Beckingham 2000) during late stages of spermiogenesis.…”
Section: Introductionmentioning
confidence: 95%
“…The peculiar molecular structure of the loop-forming regions, consisting of large portions of satellite DNA interspersed with transposable elements, is maintained in different Drosophila species, although the DNA sequences involved are very different (Hennig et al 1974;Vogt and Hennig 1983;Hujiser et al 1988;Lankenau et al 1990;Hochstenbach et al 1994). Another conserved feature of the lampbrush-like loops is their association with a number of non-Y-encoded antigens, which include DNA-interacting proteins (Marhold et al 2002), RNA-interacting proteins (Risau et al 1983;Melzer and Glätzer 1985;Bonaccorsi et al 1988;Eberhart et al 1996;Cheng et al 1998;Heatwole and Haynes 1996), and testis-specific antigens that are incorporated either in nuclei (Svensson et al 2003) or in sperm tails (Hulsebos et al 1984;Bonaccorsi et al 1988;Pisano et al 1993;Lu and Beckingham 2000) during late stages of spermiogenesis.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, one cannot exclude the possibility that the histones are at least partially bound to transcripts. Finally, it should be noted that, in immunological studies, a variety of proteins have been reported to be present in the Ychromosomal lampbrush loops (Hulsebos et al 1984 …”
Section: Accessibility Of the H33-specific Epitope In Chromatinmentioning
confidence: 99%
“…They were then rinsed in PBS and processed immediately for immunofluorescence. RNase A (100 ,ug/ml) and RNase T1 (50 units/ml) were used together in 0.3 M NaCl/0.03 M sodium citrate, pH 7.0.Immature oocytes from Acheta and Achaearanea were isolated in OR2 saline (11) and squashed between a microscope slide and coverslip as described (12). The slide was frozen in liquid N2, the coverslip was pried off with a razor blade, and the preparation was postfixed in 2% paraformaldehyde in 95% (vol/vol) ethanol for 30 min.…”
mentioning
confidence: 99%